Chronic stress, neuroinflammation, and depression: an overview of pathophysiological mechanisms and emerging anti-inflammatories - Hassamal, Sameer (Frontiers in Psychiatry, 2023)
In a subset of patients, chronic exposure to stress is an etiological risk factor for neuroinflammation and depression. Neuroinflammation affects up to 27% of patients with MDD and is associated with a more severe, chronic, and treatment-resistant trajectory. Inflammation is not unique to depression and has transdiagnostic effects suggesting a shared etiological risk factor underlying psychopathologies and metabolic disorders. Research supports an association but not necessarily a causation with depression. Putative mechanisms link chronic stress to dysregulation of the HPA axis and immune cell glucocorticoid resistance resulting in hyperactivation of the peripheral immune system. The chronic extracellular release of DAMPs and immune cell DAMP-PRR signaling creates a feed forward loop that accelerates peripheral and central inflammation. Higher plasma levels of inflammatory cytokines, most consistently interleukin IL-1β, IL-6, and TNF-α, are correlated with greater depressive symptomatology. Cytokines sensitize the HPA axis, disrupt the negative feedback loop, and further propagate inflammatory reactions. Peripheral inflammation exacerbates central inflammation (neuroinflammation) through several mechanisms including disruption of the blood-brain barrier, immune cellular trafficking, and activation of glial cells. Activated glial cells release cytokines, chemokines, and reactive oxygen and nitrogen species into the extra-synaptic space dysregulating neurotransmitter systems, imbalancing the excitatory to inhibitory ratio, and disrupting neural circuitry plasticity and adaptation. In particular, microglial activation and toxicity plays a central role in the pathophysiology of neuroinflammation. Magnetic resonance imaging (MRI) studies most consistently show reduced hippocampal volumes. Neural circuitry dysfunction such as hypoactivation between the ventral striatum and the ventromedial prefrontal cortex underlies the melancholic phenotype of depression. Chronic administration of monoamine-based antidepressants counters the inflammatory response, but with a delayed therapeutic onset. Therapeutics targeting cell mediated immunity, generalized and specific inflammatory signaling pathways, and nitro-oxidative stress have enormous potential to advance the treatment landscape. Future clinical trials will need to include immune system perturbations as biomarker outcome measures to facilitate novel antidepressant development. In this overview, we explore the inflammatory correlates of depression and elucidate pathomechanisms to facilitate the development of novel biomarkers and therapeutics.